2016
DOI: 10.1111/pce.12643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat and drought stress on post‐illumination bursts of volatile organic compounds in isoprene‐emitting and non‐emitting poplar

Abstract: Over the last decades, post‐illumination bursts (PIBs) of isoprene, acetaldehyde and green leaf volatiles (GLVs) following rapid light‐to‐dark transitions have been reported for a variety of different plant species. However, the mechanisms triggering their release still remain unclear. Here we measured PIBs of isoprene‐emitting (IE) and isoprene non‐emitting (NE) grey poplar plants grown under different climate scenarios (ambient control and three scenarios with elevated CO2 concentrations: elevated control, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 74 publications
(142 reference statements)
4
33
0
Order By: Relevance
“…The 2015 OH reactivity maximum occurred during the lightdark transition of sunset. Several studies have shown VOC bursts of isoprene, acetaldehyde, and/or (stress-related) greenleaf volatiles after light-dark transitions (Karl et al, 2002;Graus et al, 2004;Hayward et al, 2004;Brilli et al, 2011;Jardine et al, 2012;Jud et al, 2016). These so-called "post-illumination bursts" are thought to be associated with fast changes in intracellular pH in fast light-to-dark-transitions (Brilli et al, 2011), a "pyruvate overflow mechanism" (Karl et al, 2002;Hayward et al, 2004), or a "pyruvate dehydrogenase bypass pathway" (Jardine et al, 2012).…”
Section: Other Stress-induced Bvoc Emissionsmentioning
confidence: 99%
“…The 2015 OH reactivity maximum occurred during the lightdark transition of sunset. Several studies have shown VOC bursts of isoprene, acetaldehyde, and/or (stress-related) greenleaf volatiles after light-dark transitions (Karl et al, 2002;Graus et al, 2004;Hayward et al, 2004;Brilli et al, 2011;Jardine et al, 2012;Jud et al, 2016). These so-called "post-illumination bursts" are thought to be associated with fast changes in intracellular pH in fast light-to-dark-transitions (Brilli et al, 2011), a "pyruvate overflow mechanism" (Karl et al, 2002;Hayward et al, 2004), or a "pyruvate dehydrogenase bypass pathway" (Jardine et al, 2012).…”
Section: Other Stress-induced Bvoc Emissionsmentioning
confidence: 99%
“…Electroantennographic studies showed that formic and acetic acids elicit psyllid antennal responses (George et al, 2016), and act as phagostimulants that increase psyllid probing/feeding behavior (Lapointe et al, 2016). Other studies reported that photochemical oxidation of VOCs in general can lead to formation of a wide range of gaseous reaction or aerosol products (Bergström et al, 2014;Jud et al, 2016). These oxidative products may have ecological consequences for plantinsect interactions, when plant surfaces are exposed by gaseous contact or direct deposition.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is most likely due to the reduced availability of the substrate of the relevant biosynthetic pathways due to strongly impaired photosynthesis. In contrast, emission of stress-induced compounds, such as sesquiterpenes or green leaf volatiles (products of the lipoxygenase reaction) can increase in response to drought stress [65,72]. The results of our simulations could be affected by better considering the influence of drought and heat on BVOC emission, which most likely strongly depends on individual tree species' drought sensitivity.…”
mentioning
confidence: 97%
“…Several studies have indicated that moderately reduced soil water availability does not affect or rather slightly stimulates isoprenoid emissions [65][66][67]. In contrast, strongly reduced water availability affects the biosynthesis of isoprenoids, thereby decreasing their emissions [66][67][68][69][70][71][72][73]. This effect is most likely due to the reduced availability of the substrate of the relevant biosynthetic pathways due to strongly impaired photosynthesis.…”
mentioning
confidence: 99%